Język „runglijski” i auto-odpowiadacz: środki komizmu w opowiadaniach Jurija Drużnikowa - Niefagina, Galina (Studia Rossica Posnaniensia, 2012)
Yuri Druzhnikov belongs to the ironic-realistic trend in the prose of the 20th–21st century. An analysis of the stories in the book There is to You Not Here! allows one to draw a conclusion that the basic comic means are: at a composition level – the story construction (by using the joke principle), presenting a situation as an actual event and its addition or specification at the level of style – metaphor or phraseological unit, specification, a concrete definition of citations, popular expressions, and at the language level – a mixture of different languages – Runglish.